Potencial neuroimunomodulatório do ácido cafeico sobre o sistema purinérgico e colinérgico em modelo in vitro e in vivo de diabetes - Castro, Milagros Fanny Vera (2024)
Type 1 Diabetes Mellitus (DM) is a metabolic disorder characterized by high blood glucose levels (hyperglycemia), resulting from the lack of insulin production due to the selfdestruction of pancreatic β cells. Thus, hyperglycemia can lead to changes in the structure and physiology of the brain, mainly in regions involved in the formation, organization, and storage of memories. These changes represent a complication of diabetes, which is called Diabetic Encephalopathy. In this context, the purinergic and cholinergic signaling pathways play important roles in the modulation of several functions of the central nervous system (CNS). To control neurodegenerative and neuroinflammatory processes, as well as to reduce the incidence of cognitive impairment in DM, therapies with natural compounds have been the focus of investigations. In this sense, caffeic acid (CA) is a phenolic compound known to have a broad spectrum of pharmacological activities. Thus, this study aimed to evaluate the neuroimmunomodulatory potential of CA, as well as the possible involvement of its mechanism of action in the cholinergic and purinergic systems and inflammatory markers, through two experimental protocols in vivo and in vitro. In protocol I, in vivo, we explored the effect of CA treatment (10 and 50 mg/kg) on the purinergic and cholinergic signaling pathway associated with learning and spatial memory in diabetic rats induced by streptozotocin (STZ) 55 mg/kg intraperitoneally (CEUA: 5635030516). The results showed that CA: a) improved memory and learning deficits in diabetic rats; b) reversed the increased activity of acetylcholinesterase (AChE) and adenosine deaminase (ADA); c) increased the density of M1, α7nCh and A1 receptors; d) reduced the hydrolysis of ATP, ADP and AMP; e) reversed the increase in the density of P2X7 and A2A, as well as NLRP3, CASP1 and IL-1β; f) increased the density of IL-10 in the cortex and hippocampus of these animals. In protocol II, in vitro, we evaluated the treatment with CA (50, 75 µM) in BV-2 microglial cells exposed to high glucose concentration (25 mM), observing that a) high glucose affected the viability of BV-2; b) increased levels of nitric oxide (NO), thiobarbituric acid reactive substances (TBARS) and reactive species (RS); c) treatment with CA 75 µM per se decreased RS levels. Also in cells exposed to high glucose, CA 50 and 75 µM: d) reversed the increase in the levels of NO, TBARS, and RS; e) increased the hydrolysis of ATP, ADP, AMP, and the density of the A1 receptor; f) reversed the increase in ADA activity and the density of P2X7, A2A, and IL-1β; g) reduced cell death promoted by high glucose and the number of cells in the G0/G1 phase of the cell cycle; h) finally, CA 75 µM decreased the density of NLRP3 and IBA-1. In summary, our findings suggested that CA could improve cognitive deficit, and dysregulation of redox homeostasis, as well mitigate neuroinflammatory and neurodegenerative processes associated with altered purinergic and cholinergic signaling pathways in the diabetic state. Thus, this work aims to contribute to the search for adjuvant therapies to attenuate the mechanisms that lead to cognitive impairment presented in type 1 DM.